Pengelolaan Sampah Plastik Berbasis Ecobrick Sebagai Karya Pengrajin Masyarakat Desa Suka Karya Simeulue Tengah - Rina Mirdayanti; Zulkarnaini; Bukhari; Sandi Edo Pratama; Siti Arifa; Amy Wulandari (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Ecobricks are plastic bottles filled with non-biological waste that can be made into building blocks and crafts. Ecobrick is a collaboration-based technology that can be used as a solution to solve the plastic waste problem without incurring significant costs. This method is an innovative method to solve the problem of plastic waste that is difficult to decompose in nature. West Suka Karya Simuelue Village is a coastal area that serves as a central location for plastic waste disposal for the local community. The problem that arises is that the villagers of Suka Karya, Simeulue Tengah lack knowledge about plastic waste management. Community service activities in Suka Karya village, Simeulue Tengah are contributing to solving the problem of plastic waste management, including the production of eco-bricks with the community as a handicraft. At the end of this activity, it can be concluded that the residents of Suka Karya West Simeulue village were able to train artisans to make canvas flowers from plastic waste using the eco-bricks method.